Pembuatan Lapisan Tipis Oksida Grafena Tereduksi sebagai Material Elektroda Sistem Kapasitor dan Karakterisasinya: Vika Marcelina, Fitri Yuliasari, Yeni W Hartati, Fitrilawati, Norman Syakir - Vika Marcelina Vika Marcelina; Fitri Yuliasari Fitri Yuliasari; Yeni W Hartati Yeni W Hartati; Fitrilawati Fitrilawati; Norman Syakir Norman Syakir (Jurnal Fisika dan Aplikasinya, 2017)
Graphene is a two-dimensional carbon material and has superior mechanical, electrical, and thermal properties. Graphene has potential as an electrode material for energy storage systems such as supercapacitors. In the study used reduced graphene oxide (RGO) material obtained through the thermal reduction process of commercial graphene oxide (GO) material. The GO thin layer on the ITO-glass substrate was made using Spin coating method at 1000 rpm for 60 seconds. The RGO thin layer was obtained by heating the GO thin film at a temperature of 2000 C for 1 hour. The capacitor system uses the anode and cathode of the above RGO material and for the electrolyte medium, a 1 Molar H2SO4 solution is used. The characteristic of the capacitor system was observed by potential-static cyclic voltammetry (CV) measurements in the voltage range of -0.2-0.8 volts with a scan rate of 125 mV/s. Also performed the characteristics of charge-discharge through the measurement of charge-discharging charge in galvanostatic. Characteristic properties of energy storage are shown in the presence of a pattern of hysteresis on the CV curve. The result of the charge-discharge measurement shows a triangle curve pattern indicating the existence of a storage process of the charge. The maximum specific capacitance value of RGO electrode is 1.54 × 10-4 / mass F/g at 0.7 µA discharge current condition.